Synergistis effect of metarhizium anisopliae and fipronil on coptotermes curvignathus - Yii, Jing Ee (2016)
Termites are severe economic threats to agriculture and urban structures in the Indo- Malaysia region. As a consequence of rapid expansion of the oil palm industry on peat area, termite infestation on monoculture oil palm becomes serious and Coptotermes curvignathus is identified as the main culprit that caused palm damage and loss. In current study, an enhancement of the infectivity and application methods against termites by combining entomopathogenic fungi with sublethal dosages of pesticides as stressor to weaken the pests towards fungal infection using termite baits was introduced as management tool. In order to choose the most compatible isolate for bait formulation, the germination, vegetative growth and spore production of Metarhizium anisopliae local isolates (TA, LR2 and MG) were examined in compatibility test with several sublethal doses of fipronil. Fipronil was found compatible and relatively less detrimental to fungal growth of isolate TA. Rubber sawdust bait supplemented with glucose was developed based on feeding preference of C. curvignathus through food size and nutrient test. The formulated bait incorporated with fipronil, Metarhizium, and glucose had shown no repellence to termites. The effective shelf life of formulated bait was determined through termite virulence test and HPLC method. In the present formulation studied, the formulated bait was shown to be effective against termites up to five months of storage. The synergism in efficacy of fungus-insecticide combinations in formulated bait was determined against C. curvignathus and the results showed synergies against subterranean termite mortalities at fipronil-Metarhizium combinations of 0.05 mg a.i. L-1 fipronil with either 107 or 108 conidia g-1 in bait at 8 DPT. Moreover, with the addition of glucose in bait, synergistic effect was manisfested at 108 conidia g -1 M. anisopliae alone bait and also 0.001 mg a.i. L-1 fipronil with 108 conidia g-1 in bait. The synergy between M. anisopliae and fipronil in termites has not been reported. The insecticidal stress caused by sublethal fipronil in formulated bait may weaken the termites and reduce their defense mechanism, which facilitates fungus infection on termites. Hence, termite defensive behavioral response such as grooming, cellular immunity response, tunneling, and spatial distribution of termite cadavers after treated with formulated bait were evaluated. As the first line of termite’s defensive mechanisms, the total frequency of termite allogrooming within 72 hours post treatment was lowered down in the presence of fipronil in formulated bait which accelerated the probability of fungus infection against termites compared to the single treatment of fungus bait. Inhibition of grooming had been identified as the key factor to the enhanced infection rates. In histopathology study, C. curvignathus was proved to possess cellular immune response against fungus infection using Periodic Acid Schiff (PAS) staining. The occurrence of cellular encapsulation and melanization for termites that consumed formulated bait was lower than Metarhizium alone bait which was 45 and 65 times, respectively. The result suggested a possibility that a decrease of the cellular immune responses of termites was due to the addition of fipronil in formulated bait that weakening the immune system of termites and thereby increasing the susceptibility of termites to M. anisopliae infection. This finding can be improved in future work with more quantitative biochemical data to further prove the statement. Besides, slow action of formulated bait (fipronil 0.001 mg a.i. L-1 + Metarhizium 108 conidia g -1 + 1% glucose) was shown in infected termites which were still as active as the healthy termites in control treatment after bait feeding for three days with average tunneling speed 0.011 cm2 hour-1 termite-1. This increased the chance to create epizootic in subterranean termite colony when the disease was able to be delivered to nest by the active foragers. Another impact of fungus-insecticide combination was manifested in the spatial distribution of termite cadavers in laboratory test, whereby the infected cadavers were distributed in all primary and secondary harborages but significantly fewer in bait area. This indicated the diseases are able to disseminate to further area, presumably termite nest or satellite nests, and infect more colony members. The formulated bait was further evaluated on termite infested oil palm trees through above and underground baiting station for seven months. Rubber wood stakes consumption was used as an essential parameter to estimate the suppression of termites in the colony in underground station. The consumption of rubber wood by termites was significantly reduced 58.70% at first month post treatment of fungus-insecticide-glucose bait combination (fipronil 0.001 mg a.i. L-1 + Metarhizium 108 conidia g-1 + 1% glucose). It implied that the number of foraging termites was reduced, perhaps as a result of weakened colony. The observed synergism treatment in laboratory and field trial showed the potential for integrated fungus-insecticide control method for subterranean termite management in oil palm industry.